The watermelon boys (Cairo, Egypt Hoopoe, 2018)
It is the winter of 1915 and Iraq has been engulfed by the First World War. Hungry for independence from Ottoman rule, Ahmad leaves his peaceful family life on the banks of the Tigris to join the British-led revolt. Thousands of miles away, Welsh teenager Carwyn reluctantly enlists and is sent, via Gallipoli and Egypt, to the Mesopotamia campaign. Carwyn's and Ahmad's paths cross, and their fates are bound
Keywords: English fiction 21st century; World War, 1914-1918 Campaigns Iraq Fiction